Teleconnections of the Quasi‐Biennial Oscillation in a multi‐model ensemble of QBO‐resolving models. (15th June 2021) - Anstey, James A.; Simpson, Isla R.; Richter, Jadwiga H.; Naoe, Hiroaki; Taguchi, Masakazu; Serva, Federico; Gray, Lesley J.; Butchart, Neal; Hamilton, Kevin; Osprey, Scott; Bellprat, Omar; Braesicke, Peter; et al.
Abstract: The Quasi‐biennial Oscillation (QBO) dominates the interannual variability of the tropical stratosphere and influences other regions of the atmosphere. The high predictability of the QBO implies that its teleconnections could lead to increased skill of seasonal and decadal forecasts provided the relevant mechanisms are accurately represented in models. Here modelling and sampling uncertainties of QBO teleconnections are examined using a multi‐model ensemble of QBO‐resolving atmospheric general circulation models that have carried out a set of coordinated experiments as part of the Stratosphere‐troposphere Processes And their Role in Climate (SPARC) QBO initiative (QBOi). During Northern Hemisphere winter, the stratospheric polar vortex in most of these models strengthens when the QBO near 50 hPa is westerly and weakens when it is easterly, consistent with, but weaker than, the observed response. These weak responses are likely due to model errors, such as systematically weak QBO amplitudes near 50 hPa, affecting the teleconnection. The teleconnection to the North Atlantic Oscillation is less well captured overall, but of similar strength to the observed signal in the few models that do show it. The models do not show clear evidence of a QBO teleconnection to the Northern Hemisphere Pacific‐sector subtropical jet. Abstract : The Quasi‐Biennial Oscillation (QBO) of tropical stratospheric winds is observed to affect other regions of the atmosphere including the Northern Hemisphere stratospheric polar vortex, the North Atlantic Oscillation, and the Pacific‐sector subtropical jet. The figure shows the anomalous polar vortex winds (monthly‐mean zonal‐mean zonal wind at 10 hPa, 60°N) as a function of QBO phase (horizontal axis) and time in the seasonal cycle (vertical axis). The observed response, characterized in (a) using the JRA‐55 reanalysis, is stronger than in the models, shown in (b, c) as the multi‐model ensemble‐mean response.